2011
DOI: 10.1111/j.1442-200x.2011.03497.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive assessment of liver fibrosis in patients after the Fontan operation

Abstract: No specific parameter that reflects the progress in liver fibrosis was identified in this study. The possibility exists that type IV collagen reflects the degree of hepatic congestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Furukawa et al 16 also found that most routine liver laboratory values on serial evaluation were within normal ranges in children after Fontan, even in patients with elevated serum markers of cirrhosis. This is contrary to reports of liver laboratory abnormalities in a substantial number of Fontan patient cohorts in previous studies.…”
Section: Discussionmentioning
confidence: 91%
“…Furukawa et al 16 also found that most routine liver laboratory values on serial evaluation were within normal ranges in children after Fontan, even in patients with elevated serum markers of cirrhosis. This is contrary to reports of liver laboratory abnormalities in a substantial number of Fontan patient cohorts in previous studies.…”
Section: Discussionmentioning
confidence: 91%
“…A low cardiac index and reduced heart rate were significantly related to liver dysfunction in a Fontan patient series [91]. The IVC pressure showed a significant association with type IV collagen (a surrogate marker for hepatic fibrosis) in Fontan patients [145]. The CVP was a significant predictor of liver stiffness measured by MRE in a Fontan population [93].…”
Section: Hemodynamicsmentioning
confidence: 97%
“…39 Many of the biomarkers used to assess fibrosis in viral hepatitis have been extrapolated to FALD. 30,37,[40][41][42][43][44] The best characterized is the FibroTest (FibroSURE in the USA), which utilizes α 2 -macroglobulin, haptoglobin, GGT, bilirubin, apolipoprotein A1 and a proprietary algorithm to calculate a score predictive of fibrosis stage. [45][46][47] Most Fontan patients have significantly elevated FibroTest scores (range 0.33 to 0.82, normal r0.21), but there is poor correlation with time post-Fontan, other investigations or biopsy.…”
Section: Laboratory Testing For Faldmentioning
confidence: 99%